Is the Relationship between FDI and Environmental Degradation Nonlinear? Evidence from Tunisia and Morocco - Ghandri, Mohamed; Soltani, Hassen (Journal of Ecohumanism, 2024)
This study attempts to examine the effect of Foreign Direct Investment (FDI) on environmental degradation in Tunisia and Morocco for the period 1980- 2022. The study uses the Fully Modified Ordinary Least Squares (FMOLS) and Dynamic Ordinary Least Squares (DOLS) techniques to explore a possible non-linear relationship between FDI and environmental quality. The results of our empirical study show that FDI inflows increase environmental degradation in the long run in both of Tunisia and Morocco. This confirms the pollution heaven hypothesis. In addition, we find a non-linear relationship between FDI and environmental degradation and follows an inverted U-shape for the cases of Tunisia and Morocco. The causality results showed that there is an uni- directional causality runing from FDI to environmental degradation for the cases of Tunisia and Morocco. In terms of potential directions for the cases of Tunisia and Morocco. Future research, we strongly advise looking into government incentives and public policies related to environmental issues.